Penerapan Hukum Pidana Terhadap Kekerasan Fisik pada Istri dalam Konteks Perlindungan Korban - Indah Dwi Putri (Verdict: Journal of Law Science, 2024)
In Indonesia, domestic violence is considered an act that violates human rights and is also a form of discrimination, in accordance with the provisions contained in Article 28 of the 1945 Constitution of the Republic of Indonesia and its amendments. The purpose of this study was to determine the implementation of criminal law to physical violence against wives in the context of victim protection. The research method used was a normative juridical approach. The results of the study showed that the implementation of criminal law to physical violence against wives in the context of victim protection: a) in the form of temporary protection given for a maximum of 7 (seven) days within 1 x 24 (one time twenty-four) hours since providing protection, b) protection by advocates is given in the form of legal consultation, mediation or negotiation between the victim and the perpetrator of domestic violence. c) health services are very important in their meaning, especially in efforts to impose sanctions on perpetrators of domestic violence. d) social services are provided in the form of counseling to strengthen and provide a sense of security to victims. e) volunteer companion services are provided to victims regarding the victim's rights in order to objectively explain the domestic violence they experienced during the investigation process. f) services by spiritual guides are provided to provide explanations regarding rights and obligations and to strengthen the faith and piety of victims.